Chinese mythology and its impact on Chinese painting - Assistant Professor. Esam Nadhum Salih (Genius Journals, 2023)
This research highlights the Chinese mythology and its representation in the art of Chinese painting, this research be of four chapters
Keywords: painting; Chinese; representation